175k views
21 votes
What is the the answer for
2(x - 4)=6x

User Autokilled
by
4.7k points

2 Answers

2 votes

Answer:

x = -2

Explanation:

Step 1: Simplify both sides of the equation.

2(x−4)=6x

(2)(x)+(2)(−4)=6x (Distribute)

2x + −8 = 6x

2x − 8 = 6x

Step 2: Subtract 6x from both sides.

2x −8 − 6x = 6x − 6x

−4x − 8 = 0

Step 3: Add 8 to both sides.

−4x − 8 + 8 = 0 + 8

−4x = 8

Step 4: Divide both sides by -4.

−4x/−4

= 8/−4

x = −2

User Rishabh Singhal
by
4.7k points
12 votes

Answer:

x=-2

Explanation:

first distribute the 2 through x-4 you get 2x-8=6x then subtract 2x from both sides of the equation now you have 4x=-8 then divide 4 from both sides of the equation and you x=-2

User Toong
by
5.3k points